(untitled) (Damascus University Journal of arts and humanities sciences, 2023)
The research examines Paul Ricoeur’s presentations on the wrong human being and the issue of evil from an interpretive perspective, it aims to establish philosophical anthropology in which consideration, action, and feeling converage. Ricoeur put it on the ground of the structures of human reality in incompatibility, polarity, infinite and infinite, and the concept of moderation. Which reveals the specific fragility and vulnerability of human structure, and it introduces evil into it. Ricoeur summed it up in the concept of (immaculate) as a possibility for evil to emerge. Human beings exercise evil by their will or by their use of their freedom as imperfect and impervious beings, he admits responsibility for wrongdoing and evil. And in the question of what evil is. Ricoeur concludes that man is not the origin of evil, but "came across it and resume it". The relationship of man to evil is a relationship of conflict. Not to eliminate it, but to adapt it and